Specific Binding of Novel SPION-Based System Bearing Anti-N-Cadherin Antibodies to Prostate Tumor Cells - Karnas K (Dove Medical Press, 2021)
Karolina Karnas,1,2 Tomasz Strączek,3 Czesław Kapusta,3 Małgorzata Lekka,4 Joanna Dulińska-Litewka,2 Anna Karewicz1 1Department of Chemistry, Jagiellonian University, Kraków, Poland; 2Chair of Medical Biochemistry, Jagiellonian University Medical College, Kraków, Poland; 3AGH University of Science and Technology, Faculty of Physics and Applied Computer Science, Department of Solid State Physics, Kraków, Poland; 4Department of Biophysical Microstructures, Institute of Nuclear Physics, Polish Academy of Sciences, Kraków, PolandCorrespondence: Anna KarewiczDepartment of Chemistry, Jagiellonian University, Gronostajowa 2, Kraków, 30-387, PolandTel +48 12 686 25 33Fax +48 12 686 27 50Email karewicz@chemia.uj.edu.plJoanna Dulińska-LitewkaChair of Medical Biochemistry, Jagiellonian University Medical College, Kopernika 7, Kraków, 31-034, PolandTel +48 12 422 74 00Fax +48 12 422 32 72Email joanna.dulinska-litewka@uj.edu.plPurpose: Epithelial–mesenchymal (EMT) transition plays an important role in metastasis and is accompanied by an upregulation of N-cadherin expression. A new nanoparticulate system (SPION/CCh/N-cad) based on superparamagnetic iron oxide nanoparticles, stabilized with a cationic derivative of chitosan and surface-modified with anti-N-cadherin antibody, was synthetized for the effective capture of N-cadherin expressing circulating tumor cells (CTC).Methods: The morphology, physicochemical, and magnetic properties of the system were evaluated using dynamic light scattering (DLS), fluorescence spectroscopy, Mössbauer spectroscopy, magnetometry, and fluorescence spectroscopy. Atomic force microscopy (AFM), confocal microscopy and flow cytometry were used to study the interaction of our nanoparticulate system with N-cadherin expressed in prostate cancer cell lines (PC-3 and DU 145). A purpose-built cuvette was used in the cancer cell capture experiments.Results: The obtained nanoparticles were a spherical, stable colloid, and exhibited excellent magnetic properties. Biological experiments confirmed that the novel SPION/CCh/N-cad system interacts specifically with N-cadherin present on the cell surface. Preliminary studies on the magnetic capture of PC-3 cells using the obtained nanoparticles were successful. Incubation times as short as 1 minute were sufficient for the synthesized system to effectively bind to the PC-3 cells.Conclusion: Results obtained for our system suggest a possibility of using it to capture CTC in the flow conditions.Keywords: superparamagnetic iron oxide nanoparticles, N-cadherin, antibody, circulating tumor cells, cancer, magnetic cell capture